2018
DOI: 10.1039/c8nj03632b
|View full text |Cite
|
Sign up to set email alerts
|

Two isomers of a bis(diphenylphosphino)phosphinine, and the synthesis and reactivity of Ru arene/Cp* phosphinophosphinine complexes

Abstract: Two isomers of a bis(diphenylphosphino)phosphinine have been synthesised, and the Ru coordination chemistry of a 2-phosphinophosphinine extended to include reactions of H2O across a PC double bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 102 publications
1
13
0
Order By: Relevance
“…Single crystal X-ray diffraction revealed the anticipated molecular structure (Figure 3). The phosphinine ring was planar with C-C bond lengths similar to those observed in other aromatic phosphinine rings [18,19,36] and benzene. The P-C bond lengths in the ring (1.7516(17) and 1.7282(18) Å) were shorter than the P-C bond length to the PPh 2 substituent (1.8235(17) Å).…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…Single crystal X-ray diffraction revealed the anticipated molecular structure (Figure 3). The phosphinine ring was planar with C-C bond lengths similar to those observed in other aromatic phosphinine rings [18,19,36] and benzene. The P-C bond lengths in the ring (1.7516(17) and 1.7282(18) Å) were shorter than the P-C bond length to the PPh 2 substituent (1.8235(17) Å).…”
Section: Resultssupporting
confidence: 60%
“…The characterisation of 8 was performed by mass spectrometry (accurate mass determined for [M + H] + ) and by single crystal X-ray diffraction. The molecular structure (Figure 2) revealed disorder in the central phosphinine ring over an inversion centre situated in the middle of the molecule, as was seen in the structure of 5 [36], which prevented a detailed assessment of the bond lengths and angles in the ring. The P=Se bond lengths were determined to be 2.1097(5) Å.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…46 Previous work in our group has demonstrated that Ru catalysts based on the bidentate chelating phosphinophosphinine ligand 2-PPh 2 -3-Me-6-SiMe 3 -PC 5 H 2 (PP′) catalysed the room temperature transfer hydrogenation of acetophenone and the H-borrowing upgrading of alcohol fuels. 46,51 Ruthenium hydrides are implicated in many catalytic reactions, yet the first Ru complex comprising of both a hydride and phosphinine ligand has only been described recently by us. 52 Herein, we describe the first ruthenium phosphinine dihydride complex and compare its catalytic activity to that of classical diphosphine-supported complexes for AD reactions.…”
mentioning
confidence: 99%